HDR Brachytherapy and SBRT as Bridging Therapy to Liver Transplantation in HCC Patients: A Single-Center Experience - Walter, Franziska; Fuchs, Frederik; Gerum, Sabine; Rottler, Maya C.; Erdelkamp, Robert; Neumann, Jens; Nierer, Lukas; Guba, Markus; De Toni, Enrico N.; Seidensticker, Max; Ricke, Jens; Belka, Claus; et al. (Frontiers in Oncology, 2021)
Background In the treatment of patients with HCC awaiting liver transplantation (LT), local ablative treatments (LAT) are available either for downstaging or as bridging treatment. We present our clinical experience with both available radiation-based techniques, brachytherapy (BT), and stereotactic body radiotherapy (SBRT). Methods All patients diagnosed with HCC and who were treated with BT or SBRT at our institution between 2011 and 2018 were retrospectively reviewed. The current analysis included all patients who subsequently underwent LT. Results A total of 14 patients (male=9; female=5) were evaluated. Seven underwent BT for bridging before LT, and seven were treated with SBRT. BT was performed with a prescribed dose of 1 × 15 Gy, while SBRT was applied with 37 Gy (65%-iso) in three fractions in six patients, and one patient was treated with 54 Gy (100%-iso) in nine fractions. The treatment was generally well tolerated. One case of grade 3 bleeding was reported after BT, and one case of liver failure occurred following SBRT. All patients underwent LT after a median time interval of 152 days (range 47–311) after BT and 202 days (range 44–775) following SBRT. In eight cases, no viable tumor was found in the explanted liver, while four liver specimens showed vital tumor. The median follow-up after SBRT was 41 months and 17 months following BT. Overall, no hepatic HCC recurrence occurred following LT. Conclusion Both SBRT and BT are feasible and well tolerated as bridging to LT when applied with caution in patients with impaired liver function. Radiation-based treatments can close the gap for patients not suitable for other locally ablative treatment options.